Successful renal retransplantation after graft loss from BK polyomavirus infection in a human immunodeficiency virus‐positive patient. Issue 6 (10th November 2016) - Barthélemy, Aurore; Bouvier, Nicolas; Verdon, Renaud; Chatelet, Valérie; Hurault de Ligny, Bruno
Abstract: We report the case of a human immunodeficiency virus‐seropositive patient whose initial kidney transplant failed because of BK polyomavirus‐induced nephropathy, and who underwent a second transplantation 3 years later. BK viruria was detected 1 day after transplantation. After 1 month, BK viremia developed along with a donor‐specific antibody. After decreasing tacrolimus and mycophenolic acid and 2 courses of intravenous immunoglobulins, BK viremia and donor‐specific antibody permanently disappeared, with stable renal function.